REVERSED-PHASE-HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION FOR SIMULTANEOUS ESTIMATION OF RUTIN AND QUERCETIN AS WELL AS PHARMACOKINETIC EVALUATION IN RAT PLASMA - PRASHANT S KUMBHAR; BIMLESH KUMAR; SAFINA I MULLA; GANESH MOTE; DILEEP SINGH BAGHEL (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Rutin and quercetin are widely present flavonoids in many herbal extracts, with potential therapeutic benefits in various diseases. Their pharmacokinetic interactions and combined effects on bioavailability have not been extensively studied. This research aims to develop and validate a bioanalytical method for studying the pharmacokinetic interactions between rutin and quercetin in rats and to estimate their plasma concentration when administered alone and in combination. Methods: In this study, a bioanalytical method was developed and validated for interflavonoid combination. Pharmacokinetic interactions of rutin and quercetin were estimated using six rats, and divided into three groups for a pharmacokinetic interaction study between R (100 mg/kg) and Q (40 mg/ kg), administered alone as well as in combination. The total plasma concentration of rutin and quercetin was determined by the high-performance liquid chromatography method. The estimation method was developed and validated using international council for harmonization guidelines. Results: The outcomes of these studies show characteristic differences in the pharmacokinetics of rutin and quercetin. The bioavailability of quercetin increased compared to the bioavailability of rutin. The maximum plasma concentration of Q in combination was 736.3058621 μg/mL×h, whereas it was 675.0596359 μg/mL×h when given alone. In the case of rutin, the maximum plasma concentration was 323.585 μg/mL×h in combination, and 319.1925 μg/mL×h when administered alone. From the outcomes, it was proven and estimated that there is an interflavonoid interaction between rutin and quercetin. The possible interaction between the two flavone constituents with hydrolyzing enzymes in their combination enhances bioavailability. Conclusion: It is concluded that if both drugs are used in combination, they may produce a beneficial effect in the treatment of neuropathic pain